Modulation of Phenylalanine and Tyrosine Metabolism in HIV-1 Infected Patients with Neurocognitive Impairment: Results from a Clinical Trial - Giuseppe P. Innocenti; Letizia Santinelli; Luca Laghi; Cristian Borrazzo; Claudia Pinacchio; Mariangela Fratino; Luigi Celani; Eugenio N. Cavallari; Carolina Scagnolari; Federica Frasca; Guido Antonelli; Claudio M. Mastroianni; et al. (Metabolites, 2020)
To investigate the effects of oral bacteriotherapy on intestinal phenylalanine and tyrosine metabolism, in this longitudinal, double-arm trial, 15 virally suppressed HIV+ individuals underwent blood and fecal sample collection at baseline and after 6 months of oral bacteriotherapy. A baseline fecal sample was collected from 15 healthy individuals and served as control group for the baseline levels of fecal phenylalanine and tyrosine. CD4 and CD8 immune activation (CD38+) was evaluated by flow cytometry. Amino acid evaluation on fecal samples was conducted by Proton Nuclear Magnetic Resonance. Results showed that HIV+ participants displayed higher baseline phenylalanine/tyrosine ratio values than healthy volunteers. A significand reduction in phenylalanine/tyrosine ratio and peripheral CD4+ CD38+ activation was observed at the end of oral bacteriotherapy. In conclusion, probiotics beneficially affect the immune activation of HIV+ individuals. Therefore, the restoration of intestinal amino acid metabolism could represent the mechanisms through which probiotics exert these desirable effects.